Child Talk, Adult Power: A Conversation Analysis of The Boss Baby Movie - Mubarok, Tyas Alhim (Kajian Linguistik dan Sastra, 2025)
This study examines the interplay of language, authority, and identity in the animated film The Boss Baby through the lens of conversation analysis. Focusing on the film’s unique premise, an infant who speaks and behaves like an adult. The research explores how linguistic features such as turn-taking, speech acts, and power dynamics are employed to construct and challenge traditional roles of childhood and adulthood. This research employs a qualitative method grounded in the principles of Conversation Analysis. By analyzing selected dialogues between the titular baby and other characters, this paper reveals how adult-like language is used to subvert expectations, assert dominance, and create comedic tension. The findings highlight how The Boss Baby uses conversation as a tool to blur age-based hierarchies, offering insights into how media narratives shape and reflect societal understandings of power and communication. Abstrak Penelitian ini meneliti interaksi bahasa, otoritas, dan identitas dalam film animasi The Boss Baby melalui lensa analisis percakapan. Berfokus pada premis unik film tersebut, seorang bayi yang berbicara dan berperilaku seperti orang dewasa. Penelitian ini mengeksplorasi bagaimana fitur linguistik seperti giliran bicara, tindakan bicara, dan dinamika kekuasaan digunakan untuk membangun dan menantang peran tradisional masa kanak-kanak dan dewasa. Penelitian ini menggunakan metode kualitatif yang didasarkan pada prinsip-prinsip Analisis Percakapan. Dengan menganalisis dialog terpilih antara bayi tituler dan karakter lain, penelitian ini mengungkap bagaimana bahasa seperti orang dewasa digunakan untuk menumbangkan harapan, menegaskan dominasi, dan menciptakan ketegangan komedi. Temuan tersebut menyoroti bagaimana The Boss Baby menggunakan percakapan sebagai alat untuk mengaburkan hierarki berbasis usia, menawarkan wawasan tentang bagaimana narasi media membentuk dan mencerminkan pemahaman masyarakat tentang kekuasaan dan komunikasi.